The Effect of Inquiry-Based Learning Model by Jas Approach on Students’ Scientific Process Skills - Rahmawati, Nur Fitria; Alimah, Siti; Utami, Nur Rahayu (Journal of Biology Education, 2017)
This Study aimed to determine the effect of guided inquiry-based learning model with Natural Environment Exploration (JAS) approach on the topic of sensory system on student’s Sciencetific Process Skills (SPS) as well as determining the increase of students’ SPS. The type of this study was quasi-experimental with non-equivalent control group design. Subjects in this study were students from grade XI of class MIA 4 as the control and XI MIA 5 as the treatment group. The independent variable was the guided inquiry-based learning model with JAS approach on the topic of sensory system, while the dependent variable was students’ SPS. Students’ SPS was measured by pre-test and post-test consist of 30 questions. The result of data analysis showed that the guided inquiry-based learning model with JAS approach had a significant effect on students’ SPS, with the value of determination coefficient at 0.374. Students’ SPS increased after the treatment with the average N-gain of treatment group at 0.27. The result of the study concludes that the implementation of guided inquiry-based learning model by JAS approach on the topic of sensory system affects and increases the students’ SPS, especially in the aspect of interpreting data, communicating, designing experiment, formulating hypotheses and classifying